Token morphing as a manifestation of the liberalization of the SEC’s regulatory approach to cryptocurrencies (Discourse of Law and Administration, 2024)
The article discusses the change in the approach of the US Securities and Exchange Commission (SEC) to regulating cryptocurrencies. The author draws attention to the introduction by the SEC of a new institution called „token morphing”. The result of morphing is that the cryptocurrency loses its security status. The institution in question is therefore an expression of a departure from the currently dominant regulatory narrative, according to which the vast majority of cryptocurrencies available on the market constitute a securities offering. Changing this narrative may undoubtedly prove to be very beneficial for the development of innovation in the blockchain and cryptocurrency sector. At the same time, the author lists the ambiguities that accompany the application of this still young concept and proposes to deepen work on its development in order to guarantee such a fundamental postulate proclaimed by legal theories, which is its certainty.
Keywords: blockchain; securities; decentralization; Securities Act; investment contract